Estrategias didácticas para el ámbito del descubrimiento del medio natural y cultural en primer grado de educación general básica en la Escuela 30 de Octubre - Cabascango Yamberla, María Rosa (2018)
He aim of this degree work is to carry out a methodological proposal in which didactic strategies for the discovery of the natural and cultural environment in the first grade of Basic General Education of the 30 de Octubre School are proposed. The purpose of developing teaching strategies is to provide the teacher with the teaching process and ensure that students acquire optimal learning according to the planning. After the observation made to the educational institution the deficiency of didactic strategies for the field of the discovery of the natural and cultural environment in the aforementioned group was evidenced. The methodology used to carry out the titling work is scientific research whose purpose is to provide first grade teachers with a practical compilation of teaching strategies with activities to develop a pedagogical tour guide. The methodological proposal is made up of the theoretical and conceptual foundation, in which concepts that will be used in the process of developing the teaching strategies are presented. The second part consists of four activities to develop a guide of pedagogical visits for the field of discovery of the natural and cultural environment that facilitates the teaching process to first grade teachers of Basic General Education. And finally, the conclusions reached after the non-participant observation of the first grade teacher.